Episteme de negras: o samba de pareia como fundamento identitário - Santos, Jouse Mara Ferreira (2024)
The writing of this research is marked by my condition of being a black, Candomblé woman in Sergipe society, especially in my relationship with the quilombola community Mussuca and Samba de Pareia. Samba de pareia is a Mussuquense, black-Brazilian cultural practice, formed primarily by women from the quilombola community, Mussuca, in Sergipe, which takes place with the intention of celebrating the birth of children within this community. The research follows my personal route in which I refer to the life stories of these Mussuquense women to highlight themes such as: ancestry, affirmative black identity formation, subjectivities, healing and epistemologies arising from black experiences. We sought to understand to what extent the experiences felt by the quilombola women of Samba de Pareia da Mussuca and my personal experiences can be seen as survival strategies and as contributions to the affirmative construction of black cultural identity. In terms of methodology, actions were carried out such as: literature review, consultation of periodicals, study of academic works related to the theme, analysis of audiovisual material, in addition to field visits, fundamental moments that involved conducting interviews, informal conversations, observation of festivity. Oral history, Afrocentricity and Afroperspective provided a reflective basis that allowed me to enter the matripotent mythical-philosophical-ancestral terrain present in the lives of these women.